Peningkatan Kesadaran Pengelolaan Sampah Kampus Unsulbar melalui Edukasi dan Kampanye Pemilahan Sampah Organik dan Anorganik - Rezky Ramadhan Antuli; Asma Amin; Wandi Abbas (PELITA NUSA TENGGARA, 2026)
Waste management challenges at the University of West Sulawesi (Unsulbar) are primarily driven by low awareness, limited knowledge, and inconsistent waste-sorting practices among campus communities. This community service program aims to enhance the capacity of students, lecturers, administrative staff, and cleaning personnel through educational interventions, environmental campaigns, and the provision of organic–inorganic waste-sorting facilities. The methods included an initial survey, interactive socialization sessions, practical demonstrations, group discussions, installation of categorized waste bins, and on-site mentoring. The results indicate a significant improvement in participants’ knowledge, attitudes, and skills in waste sorting. Post-intervention observations show positive behavioral changes, reflected in the increased accuracy of waste disposal and stronger commitment to adopting 3R practices. The program demonstrates that combining educational approaches with facilities and campaign activities is effective in fostering a more responsible environmental culture within higher education institutions. Sustaining this progress requires continuous monitoring and alignment of waste-sorting behavior with the campus waste-management system.